2022
DOI: 10.26434/chemrxiv-2022-rmf6x-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A headspace collection chamber for whole body volatilomics

Abstract: The human body secretes a complex blend of volatile organic compounds (VOCs) via the skin, breath and bodily fluids, the study of which can provide valuable insight into the physiological and metabolic state of an individual. Methods to profile human-derived volatiles typically source VOCs from bodily fluids, exhaled breath or skin of isolated body parts. To facilitate profiling the whole body volatilome, we have engineered a sampling chamber that enables the collection and analysis of headspace from the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…We next leveraged our previous analyses of human whole body headspace 48 to target the primary chemical constituents of human whole body odor, confirming the identity of 40 known VOCs detected in whole body odor in this semi-field dataset (Fig. S12).…”
Section: Integrative Use Of Whole Body Odor Volatilomics Identifies C...supporting
confidence: 66%
See 3 more Smart Citations
“…We next leveraged our previous analyses of human whole body headspace 48 to target the primary chemical constituents of human whole body odor, confirming the identity of 40 known VOCs detected in whole body odor in this semi-field dataset (Fig. S12).…”
Section: Integrative Use Of Whole Body Odor Volatilomics Identifies C...supporting
confidence: 66%
“…These results coupled with the hierarchical nature of behavioral preferences shown by An. gambiae to olfactory stimuli of increasing chemical complexity, suggest that at enhanced spatial scales, multi-sensory integration between visual cues, heat, CO2 and other human body odorants 23,46,[53][54][55] The human body emits hundreds of volatile organic compounds (VOCs) in exhaled breath and skin emissions 64 , and our prior research has demonstrated considerable heterogeneity in the chemical complexity of whole body emissions between humans 48 . This natural variation in the types and abundances of VOCs emitted by the human body has long been hypothesized as a key factor driving mosquito host preference 65 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations